Improvement of E-Learning Based On Hybrid Learning Methods At The University In The Era Of Industrial Revolution 4.0 - Sutiah,Supriyono (International Journal of Advanced Science and Technology, 2020)
Improved quality of learning indeed varies following the situation and conditions in institutions and policy leadership. Research methods used in this research will result in improved quality of learning techniques online. The results of this research can be shown in the level of success of the e-learning process with the results of testing the application of hybrid learning methods reaching is better. The e-learning process can be said to be effective if the needs and analysis result as expected. Efficiency and effectiveness may be following the real conditions that occur at an educational institution. The results of research still need to be improved to increase compliance with the process that exists in the world of education as well as a debilitation media online learning can be resolved or minimized. The results of this accuracy can be increased again by conducting a combination of learning mechanisms.